The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/mc.23413
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stage‐specific tumor progression in TMPRSS2‐ERG (fusion)‐driven and non‐fusion‐driven prostate cancer in GEM models

Abstract: In the present study, we performed a comparative stage-specific pathological and molecular marker evaluation of TMPRSS2-ERG fusion and PTEN loss-driven (TMPRSS2-ERG. Pten flox/flox ) versus non-fusion-driven prostate tumorigenesis (Hi-Myc) in mice. Anterior, ventral, and dorsolateral prostates were collected from mice at different ages (or time points post-Cre induction). Results indicated that growth and progression of prostatic intraepithelial lesions to adenocarcinoma stages occurred in both mice models alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…Brown-stained cells were counted as positive cells (among total number of cells) and plotted as % positive cells; these were counted in five randomly selected fields at ×400 magnification. Immunoreactivity (intensity of brown staining was represented by arbitrary values) was noted as 0 (no staining), +1 (weak intensity), +2 (moderate intensity), +3 (strong intensity), and +4 (very strong intensity) [ 25 ]. Immunopositive area was assessed as the proportion area of prostate which is positive for expression and assigned arbitrary scores as 0 (<5% positive area), +1 (5–25% positive area), +2 (26–50% positive area), +3 (51–75% positive area), and +4 (>75% positive area).…”
Section: Methodsmentioning
confidence: 99%
“…Brown-stained cells were counted as positive cells (among total number of cells) and plotted as % positive cells; these were counted in five randomly selected fields at ×400 magnification. Immunoreactivity (intensity of brown staining was represented by arbitrary values) was noted as 0 (no staining), +1 (weak intensity), +2 (moderate intensity), +3 (strong intensity), and +4 (very strong intensity) [ 25 ]. Immunopositive area was assessed as the proportion area of prostate which is positive for expression and assigned arbitrary scores as 0 (<5% positive area), +1 (5–25% positive area), +2 (26–50% positive area), +3 (51–75% positive area), and +4 (>75% positive area).…”
Section: Methodsmentioning
confidence: 99%
“…Pten flox/flox ) we identified that indeed NSAIDs, aspirin and naproxen, have strong efficacy in reducing prostate tumorigenesis in the TMPRSS2-ERG driven PCa model but not in the non-TMPRSS2-ERG driven (Hi-Myc +/− mouse) PCa model. 4 We also established in the same study that the NSAIDs primarily affect proliferation in the TMPRSS2-ERG fusion driven cancers, which could possibly stem from the NSAIDs-mediated decrease in androgen receptor (AR) expression. 4 This is because of the androgen sensitivity of the TMPRSS2 promoter; specifically, after TMPRSS2-ERG fusion, the androgen-bound AR binds to TMPRSS2 regions, and results in ERG overexpression which in turn causes overexpression/activation of proliferative pathways.…”
mentioning
confidence: 90%
“…4 We also established in the same study that the NSAIDs primarily affect proliferation in the TMPRSS2-ERG fusion driven cancers, which could possibly stem from the NSAIDs-mediated decrease in androgen receptor (AR) expression. 4 This is because of the androgen sensitivity of the TMPRSS2 promoter; specifically, after TMPRSS2-ERG fusion, the androgen-bound AR binds to TMPRSS2 regions, and results in ERG overexpression which in turn causes overexpression/activation of proliferative pathways. 5 Another important factor that cannot be overlooked is that cancer progression is a complex process; many pathways associated with cancer initiation and progression are similar to inflammation and wound healing.…”
mentioning
confidence: 90%
See 2 more Smart Citations